The unfinished revolution Sun Yat-Sen and the struggle for modern China - Tjio, Kayloe (Marshall Cavendish Editions, 2017)
The Unfinished Revolution is a superb new biography of Sun Yat-sen, whose life, like the confusion of his time, is not easy to interpret. His political career was marked mostly by setbacks, yet he became a cult figure in China after his death. Today he is the only 20th-century Chinese leader to be widely revered on both sides of the Taiwan Strait. In contrast, many Western historians see little in his ideas or deeds to warrant such high esteem. This book presents the most balanced account of Sun to date, one that situates him within the historical events and intellectual climate of his time. Born in the shadow of the Opium War, the young Sun saw China repeatedly humiliated in clashes with foreign powers, resulting in the loss of territory and sovereignty. When his efforts to petition the decrepit Manchu court to institute reforms failed, Sun took to revolution. Sun traversed the globe to canvass support for his cause. A notable feature of the book is its coverage of the overseas Chinese in Southeast Asia and their contributions to his uprisings on the mainland, which set the stage for the overthrow of two millennia of imperial rule in 1911. But Sun's vision of China was not to be. Within a few years the republic was hijacked and plunged into chaos. This fascinating and immensely readable work illuminates the man and his achievements, his strengths and his weaknesses, revealing how he came to spearhead the revolution that would transform his country and yet, at his death in 1925 and still today, remain agonizingly unfinished. "I've read at least 30 or 40 biographies of Sun Yat Sen in my life, so I was intrigued to find out what Kayloe had to say that's new. I was fascinated. He really tells the story afresh. Through a lively series of chapters that capture different phases of Sun's life and career, Kayloe tries to understand and to convey to us.